Intersectional (in) equities in contact coverage of maternal and newborn health services in Nepal: insights from a nationwide cross-sectional household survey - Resham B. Khatri; Yibeltal Alemu; Melinda M. Protani; Rajendra Karkee; Jo Durham (BMC, 2021)
Abstract Background Persistent inequities in coverage of maternal and newborn health (MNH) services continue to pose a major challenge to the health-care system in Nepal. This paper uses a novel composite indicator of intersectional (dis) advantages to examine how different (in) equity markers intersect to create (in) equities in contact coverage of MNH services across the continuum of care (CoC) in Nepal. Methods A secondary analysis was conducted among 1978 women aged 15-49 years who had a live birth in the two years preceding the survey. Data were derived from the Nepal Demographic and Health Survey (NDHS) 2016. The three outcome variables included were 1) at least four antenatal care (4ANC) visits, 2) institutional delivery, and 3) postnatal care (PNC) consult for newborns and mothers within 48 h of childbirth. Independent variables were wealth status, education, ethnicity, languages, residence, and marginalisation status. Intersectional (dis) advantages were created using three socioeconomic variables (wealth status, level of education and ethnicity of women). Binomial logistic regression analysis was employed to identify the patterns of (in) equities in contact coverage of MNH services across the CoC. Results The contact coverage of 4ANC visits, institutional delivery, and PNC visit was 72, 64, and 51% respectively. Relative to women with triple disadvantage, the odds of contact coverage of 4ANC visits was more than five-fold higher (Adjusted Odds Ratio (aOR) = 5.51; 95% CI: 2.85, 10.64) among women with triple forms of advantages (literate and advantaged ethnicity and higher wealth status). Women with triple advantages were seven-fold more likely to give birth in a health institution (aOR = 7.32; 95% CI: 3.66, 14.63). They were also four times more likely (aOR = 4.18; 95% CI: 2.40, 7.28) to receive PNC visit compared to their triple disadvantaged counterparts. Conclusions The contact coverage of routine MNH visits was low among women with social disadvantages and lowest among women with multiple forms of socioeconomic disadvantages. Tracking health service coverage among women with multiple forms of (dis) advantage can provide crucial information for designing contextual and targeted approaches to actions towards universal coverage of MNH services and improving health equity.